Human Development Index Forecasting with Moving Average, Simple Exponential Smoothing and Naïve Method - Anggraeni, Dara Puspita; Sutrasni, Ni Komang (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2023)
The purpose of this research is to forecast the Human Development Index (HDI) using the moving average (MA) method, the simple exponential smoothing method and the naïve method. The region forecasted for its HDI is North Lombok Regency, for which it has the lowest HDI in West Nusa Tenggara, Indonesia. The data used for this research is the HDI from 2010 to 2022. The selection of these methods is due to the limited amount of data and the popularity of MA, SES, and Naïve method in the world of forecasting until this day. The results of this research is the MA method which consists of MA MA3, SMA MA5, WMA MA3, WMA MA5, EMA MA3, EMA MA5, and SES tested value α=0.1 and α=0.9 and Naïve method have a high degree of accuracy that can be seen in the Mean Absolute Percentage Error (MAPE) value which is below 10%. However, the chosen method is the best method with the smallest MAPE which is Naïve method with MAPE 1.32% where MAPE is below 10% indicating that the model used is Highly accurate and the result of North Lombok Regency HDI in 2023 is 65.7 which means that the HDI in North Lombok Regency has not changed. HDI in North Lombok Regency stay on middle level